Савур-могила як концепт національної ідентичності - Яблонська, Ярина Романівна; Yablonska, Yaryna (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті на матеріалі українського фольклору та текстів романтичної й неоромантичної поезії образ Савур-могили проаналізовано як концепт національної ідентичності. Доведено, що концепт Савур-могили спонукає до роздумів про долю нації, її пам’ять, про історичні закономірності та сучасні реалії. In the article is analized the image of Savur-Mohyla as concept of national identity on the materials of Ukrainian folklore and texts of romantic and neo-romantic poetry. In particular it is found aesthetic features of national identity; it is investigated delimitation of image of Savur-Mohyla in Ukrainian folklore and literature; it is accented on the ideas of courage and sacrifice in the folk legends about the origin of Savur-Mohyla; it is analyzed the meaning of freedom and the motive test in the national Duma «Escape of three brothers from the city of Azov, from Turkish slavery» and the historical song «Oh, frost, Morozenko»; it is reproduced development of the idea of national revival in romantic poetry, that is implemented in the image of grave; it is separated category of memory, time, type (nation) in the poetic work of M. Cherniavsky « Savur-Mohyla» (1910). It is proved that the concept Savur-Mohyla encourages reflection on the fate of the nation, its memory, about historical patterns and current realities.
Savur-Mohyla as a Concept of National Identity
Keywords: концепт; національна ідентичність; легенда; переказ; дума; історична пісня; романтизм; неоромантизм; concept; national identity; legend; paraphrase; duma; historical song; romanticism; neoromanticism